1981
DOI: 10.1136/bjsm.15.3.163
|View full text |Cite
|
Sign up to set email alerts
|

Association football injuries to the brain. A preliminary report.

Abstract: In 1975 the authors sent a questionnaire to all players in the Norwegian First Division League Clubs to record the incidence of head injuries due to heading. The conclusion of the questionnaire is that there seems to be a low percentage of serious head injuries. None of the players had been operated on for epi-or subdural hematoma or other brain damage and only a few have had concussion due to heading. In sixty per cent of the players a full neurological examination and EEG recording was undertaken. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 14 publications
(15 reference statements)
1
40
1
Order By: Relevance
“…37 Top-level male soccer athletes are estimated to experience an average of 6.6 impacts per game, or 2000 head balls during games across their careers. 38 The amount of head-ball exposure during practices is unknown in this group. More recent research, however, has shown that collegiate female soccer athletes received a similar number of head balls during games (7 per game) and 3.5 headers during practice sessions.…”
Section: Discussionmentioning
confidence: 99%
“…37 Top-level male soccer athletes are estimated to experience an average of 6.6 impacts per game, or 2000 head balls during games across their careers. 38 The amount of head-ball exposure during practices is unknown in this group. More recent research, however, has shown that collegiate female soccer athletes received a similar number of head balls during games (7 per game) and 3.5 headers during practice sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently heading a soccer ball has been discussed as a source of subconcussive head impact in soccer (Koerte et al 2012(Koerte et al , 2015bLipton and Kim 2013;Jordan et al 1996). On average, professional soccer players perform 6-12 headings per game, resulting in thousands of headings over a player's career (Ekblom 1986;Rutherford et al 2009;Straume-Naesheim et al 2005;Tysvaer and Storli 1981). Because there is often no clinical manifestation, subconcussive head impacts are often thought to be harmless.…”
Section: Tmt a Trailmaking Test A Tmt B Trailmaking Test Bmentioning
confidence: 98%
“…The estimated cumulative linear (6192g) and rotational (415,036.8 rad/sec 2 ) accelerations were far below those recorded in our high school football cohort. Similarly, elite soccer athletes have been reported to sustain an average of 6.6 head balls per game (Tsyvaer and Storli, 1981). This results in approximately 264 head balls during a 40-game regular season.…”
Section: Football Head Impactsmentioning
confidence: 99%